Consider the expression. (-3)^-3 divided by 1/-6^2Which Three choices are equivalent to the expression givenA. 4/3B. 1/-(6)^2(-3)^3C. 36/-27D. -6^2/-27E. -36/(-3)^3

Respuesta :

Solution

For this case we have the following:

[tex]3^{-3}=\frac{1}{3^3}=\frac{1}{27}[/tex][tex](\frac{1}{-6})^2=\frac{1}{36}[/tex]

When we apply the division we got:

[tex]\frac{\frac{1}{27}}{\frac{1}{36}}=\frac{36}{27}=\frac{4}{3}[/tex]

Option A is correct

Option D is correct

Option E is correct

Final answer: A, D, E

ACCESS MORE